2017
DOI: 10.1186/s12872-016-0434-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional speckle-tracking echocardiography for evaluation of dilative ascending aorta biomechanics

Abstract: BackgroundTwo-dimensional (2D) echocardiography is one of the most feasible, noninvasive methods for assessing the aortic diameter and biomechanical changes. We studied possible interfaces between noninvasive biomechanical and speckle-tracking (ST) echocardiographic data from dilated aortas.MethodsAltogether, 44 patients with dilative pathology of ascending aorta (DPAA) were compared with subjects without ascending aortic dilation (diameter <40 mm). DPAA patients formed two groups based on diameter size: group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Previous studies have suggested that aortic stiffness can be deduced from echo strain-imaging. [14][15][16][17][18] Indeed, transesophageal echocardiography (TEE) studies have revealed that the aortic wall of a subset of patients with bicuspid aortic valve 14 and patients aged less than 50 years 16 is less stiff than those with tricuspid aortic valve or aged more than 50 years. However, no direct comparison between intrinsic risk factors, including ex vivo mechanics and underlying wall pathology, has been made.…”
mentioning
confidence: 99%
“…Previous studies have suggested that aortic stiffness can be deduced from echo strain-imaging. [14][15][16][17][18] Indeed, transesophageal echocardiography (TEE) studies have revealed that the aortic wall of a subset of patients with bicuspid aortic valve 14 and patients aged less than 50 years 16 is less stiff than those with tricuspid aortic valve or aged more than 50 years. However, no direct comparison between intrinsic risk factors, including ex vivo mechanics and underlying wall pathology, has been made.…”
mentioning
confidence: 99%
“…Elasticity of the aorta incorporates both the property of dilating and the property of recoiling to its initial shape. 28 Similarly, the atrial S-D relationship may provide indirect evidence of the elasticity of the RA tissue. We also speculate that during the conduit phase (when tricuspid valve remains open), the RA S-D loop may also reflect RV diastolic stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The concept was derived from torsion-displacement loop described by us and others. 28 , 29 To describe the area enclosed by torsion-volume loops, Notomi et al. coined the term “Filling Work.” They proposed that the area enclosed by the loops gives a measure of “work” being performed by the chamber and may provide a measure of the energy stored in the cardiac chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the value of STE for assessing mechanical properties of the aorta in patients with aortic aneurysms has been established. Bieseviciene et al 44 used STE to determine whether there was a difference in aortic stiffness in patients with dilative pathology of the ascending aorta (DPAA) compared to normal aortas. The group found that the ascending aortas of DPAA group with wider aortas (>45 mm) had reduced strain, reduced distensibility, and increased stiffness compared to controls.…”
Section: Ultrasound Assessment Of Aortic Biomechanicsmentioning
confidence: 99%